GROUND REALITIES OF CWSN: SCHOOLS OF PUNJAB - Dr. Poonam Beniwal , Dr. Anita Beniwal and Dipti Khokar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
After Sarva Shiksha Abhiyan the inclusive education practices have gained high momentum. Inclusion is a process by which a school expands its resources to meet the learningneeds, physical needs and emotional needs of all the children. The study was initiate a systematic self-check system for schools to find out or assess their effectiveness in terms of providing a barrier free inclusive education. It would help them keep a record of what is available and what needs to be done. The objective of the study is to study the various policies and provisions for educating children with Special Needs.To study the inclusive status of schools providing by a study of their physical environment, academic environment and social environment. Purposive sampling was used. 4 Schools that claim to be inclusive was selected. Only students identified as CWSN was selected from the sample school. A total of 10 students, 1 teacher, and 1 counsellor was selected as a sample from each school. Thus, a total of 40 students, 4 teachers and 4 counsellors were selected. A survey-based method was used for the present study The study revealed that Need to be little too the point and give some figures as to the no. of CWSN studying in these schools their experiences and efforts made by teachers to make learning better. Statement about the status of physical infrastructure, academic and social environment of the four school.